The Characteristics of Gas-Water Two-Phase Radial Flow in Clay-Silt Sediment and Effects on Hydrate Production. (12th May 2021) - Lu, Cheng; Qin, Xuwen; Yu, Lu; Geng, Lantao; Mao, Wenjing; Bian, Hang; Meng, Fanle
Abstract : Many hydrate-bearing sediments in the Shenhu area of the South China Sea are featured with unconsolidated clayed silt, small particle size, and high content of clay, which can pose a great challenge for gas production. In order to investigate the gas-water relative permeability in clay-silt sediments, through a radial flow experiment, samples from the target sediment in the Shenhu area were selected and studied. The results show that the irreducible water saturation is high and the influence of the gas-water interaction is obvious. The relative permeability analysis shows that the two-phase flow zone is narrow and maximum gas relative permeability is below 0.1. The flow pattern in clay-silt sediment is more complicated, and the existing empirical models are inadequate for flow characterization. The depressurization method to extract a hydrate reservoir with clay-silt sediments faces the problem of insufficient production capacity. Compared with the ordinary hydrate reservoir with sandstone sediment, the hydrate reservoir with clay-silt sediment has a low permeability and poor gas flow capacity. The gas-water ratio abnormally decreases during the production. It is urgent to enhance production with cost-effective measures.